Question about Casio FX-300MS Calculator

Ad

See this solution http://www.fixya.com/support/t663157-calculate_equation,

also in the case of your example:

4y=2x4 (4 times y = 2 times x times 4, moving the 4 over makes it divide by 4)

y=__2x4__ (the 4's cancel out, 4 divided by 4 = 1, 1 times anything is the same)

4

so y=2x (if we move x over it becomes divide by)

so __y__=2 (y diveided by x = 2 is as far as you can go)

x

Posted on Jun 29, 2008

Ad

Hi,

A 6ya expert can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

The service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

Good luck!

Posted on Jan 02, 2017

Ad

Apr 07, 2013 | Casio FX-115ES Scientific Calculator

Easy to verify. Put 4 instead of x in the equation. You get 2*4+4?=0. Obviously 2*4+4=3*4=12, and 12 is not equal to zero. The value x=4 is not a solution of the equation.

**2x+4=0, gives 2x=-4 and x=-4/2=-2**

Feb 08, 2012 | Office Equipment & Supplies

This should start wit X=something and Y=something, sorry I'm not an human algebra calculator....

Jul 29, 2011 | Computers & Internet

In Algebra

Likewise when you see

Special Binomial Products So when you multiply binomials you get ... Binomial Products

And we are going to look at

1. Multiplying a Binomial by Itself What happens when you square a binomial (in other words, multiply it by itself) .. ?

(a+b)2 = (a+b)(a+b) = ... ?

The result:

(a+b)2 = a2 + 2ab + b2

You can easily see why it works, in this diagram:

2. Subtract Times Subtract
And what happens if you square a binomial with a **minus** inside?

(a-b)2 = (a-b)(a-b) = ... ?

The result:

(a-b)2 = a2 - 2ab + b2

3. Add Times Subtract
And then there is one more special case... what if you multiply (a+b) by (a-b) ?

(a+b)(a-b) = ... ?

The result:

(a+b)(a-b) = a2 - b2

That was interesting! It ended up very simple.

And it is called the "**difference of two squares**" (the two squares are **a2** and **b2**).

This illustration may help you see why it works:

a2 - b2 is equal to (a+b)(a-b)
Note: it does not matter if (a-b) comes first:

(a-b)(a+b) = a2 - b2

The Three Cases
Here are the three results we just got:

(a+b)2
= a2 + 2ab + b2
} (the "perfect square trinomials")
(a-b)2
= a2 - 2ab + b2
(a+b)(a-b)
= a2 - b2
(the "difference of squares")
Remember those patterns, they will save you time and help you solve many algebra puzzles.

Using Them
So far we have just used "a" and "b", but they could be anything.

Example: (y+1)2

We can use the (a+b)2 case where "a" is y, and "b" is 1:

(y+1)2 = (y)2 + 2(y)(1) + (1)2 = y2 + 2y + 1

Example: (3x-4)2

We can use the (a-b)2 case where "a" is 3x, and "b" is 4:

(3x-4)2 = (3x)2 - 2(3x)(4) + (4)2 = 9x2 - 24x + 16

Example: (4y+2)(4y-2)

We know that the result will be the difference of two squares, because:

(a+b)(a-b) = a2 - b2

so:

(4y+2)(4y-2) = (4y)2 - (2)2 = 16y2 - 4

Sometimes you can recognize the pattern of the answer:

Example: can you work out which binomials to multiply to get 4x2 - 9

Hmmm... is that the difference of two squares?

Yes! **4x2** is **(2x)2**, and **9** is **(3)2**, so we have:

4x2 - 9 = (2x)2 - (3)2

And that can be produced by the difference of squares formula:

(a+b)(a-b) = a2 - b2

Like this ("a" is 2x, and "b" is 3):

(2x+3)(2x-3) = (2x)2 - (3)2 = 4x2 - 9

So the answer is that you can multiply **(2x+3)** and **(2x-3)** to get **4x2 - 9**

Jul 26, 2011 | Computers & Internet

That is an equation describing a straight line. The "slope-intercept" form of a line is

y = mx + b

where m is the slope (change in y-value / change in x-value)

and b is the y-intercept (the point where the line crosses the y-axis when x=0)

Positive slope means the line is rising and negative slope means it's falling.

You can rewrite the original equation 2x - 4y -9 = 0 in slope-intercept form:

y = (1/2)x - (9/4)

So you know the slope is positive 1/2 (line rises 1 y-unit for each 2 x-unit change) and crosses the y-axis at -9/4. With this information you can graph the line.

y = mx + b

where m is the slope (change in y-value / change in x-value)

and b is the y-intercept (the point where the line crosses the y-axis when x=0)

Positive slope means the line is rising and negative slope means it's falling.

You can rewrite the original equation 2x - 4y -9 = 0 in slope-intercept form:

y = (1/2)x - (9/4)

So you know the slope is positive 1/2 (line rises 1 y-unit for each 2 x-unit change) and crosses the y-axis at -9/4. With this information you can graph the line.

Jul 12, 2011 | Sewing Machines

2x + 4y = -8 ; divide each side by 2

x + 2y = -4 ; subtract x from both sides

2y = -4 - x ; rearrange

2y = -1x -4 ; divide each side by 2

y = -1/2x - 2 ; relate to slope/intercept form of line (y=mx+b)

implies there are multiple solutions that fall along a line with slope -1/2 and y intercept of -2

'

\ '

++++++++++

\ '

\ '

Sample points on this line are (-4,0), (-2,-1), (0,-2), (2,-3)

x + 2y = -4 ; subtract x from both sides

2y = -4 - x ; rearrange

2y = -1x -4 ; divide each side by 2

y = -1/2x - 2 ; relate to slope/intercept form of line (y=mx+b)

implies there are multiple solutions that fall along a line with slope -1/2 and y intercept of -2

'

\ '

++++++++++

\ '

\ '

Sample points on this line are (-4,0), (-2,-1), (0,-2), (2,-3)

Nov 04, 2010 | Mathsoft StudyWorks! Mathematics Deluxe...

Graph 2X PLUS 1 for X in open interval ]-1,0[

It should be entered as follows

(2X plus 1) (X larger than negative 1) (X less than zero)

In [Y=] editor and on line Y1= type your right hand side between parentheses (2X Plus 1). I use the Plus instead of the usual sign because the parser of the web site removes the sign.

[( ]2 [X,T,theta,n] [Plus] 1 [)] [(] [X,T,theta,n] [2nd][MATH] [3: larger than] [(-)] 1 [)] [(] [X,T,Theta,n] [2nd][MATH][5: less than] 0 [)]

Here are some screen captures to help you

It should be entered as follows

(2X plus 1) (X larger than negative 1) (X less than zero)

In [Y=] editor and on line Y1= type your right hand side between parentheses (2X Plus 1). I use the Plus instead of the usual sign because the parser of the web site removes the sign.

[( ]2 [X,T,theta,n] [Plus] 1 [)] [(] [X,T,theta,n] [2nd][MATH] [3: larger than] [(-)] 1 [)] [(] [X,T,Theta,n] [2nd][MATH][5: less than] 0 [)]

Here are some screen captures to help you

Oct 30, 2010 | Texas Instruments TI-84 Plus Calculator

You can solve it with following method.

5x+3y=6 2x-4y=5

So 5x=6-3y so 2[(6-3y)/5]-4y=5

So x=(6-3y)/5 so 12-6y-20y=25

so -26y=25-12

so -26y=13

so y= -(1/2)

2x-4y=5

so 2x=5+4y

so 2x=5+4(-1/2)

so 2x=(10-4)/2

so 2x=6/4

so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.

Thanks for using FixYa.

5x+3y=6 2x-4y=5

So 5x=6-3y so 2[(6-3y)/5]-4y=5

So x=(6-3y)/5 so 12-6y-20y=25

so -26y=25-12

so -26y=13

so y= -(1/2)

2x-4y=5

so 2x=5+4y

so 2x=5+4(-1/2)

so 2x=(10-4)/2

so 2x=6/4

so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.

Thanks for using FixYa.

Mar 03, 2010 | Office Equipment & Supplies

2x-4y=8

=> 2[x-2y]=8

=> x-2y=8/2

=>** x-2y=4**

=> 2[x-2y]=8

=> x-2y=8/2

=>

Feb 07, 2010 | Mathsoft StudyWorks! Mathematics Deluxe...

X=25-y

4(25-y) + 5y=56

100-4y+5y=56

100+y=56

y= -44

x=25+44=69

x=69 y= -44

4(25-y) + 5y=56

100-4y+5y=56

100+y=56

y= -44

x=25+44=69

x=69 y= -44

Aug 22, 2008 | Curtis-Mathis CM25011 25" TV

90 people viewed this question

Usually answered in minutes!

×